AKTUALISASI MANAJEMEN PENINGKATAN MUTU BERBASIS MADRASAH (MPMBM) - Muli Prima Aldi (STAI Nurul Falah Airmolek, 2018)
The quality of education is one of the central issues in national education. Because the quality of education is one of the pillars of human resource development, it is very important for national development. It can even be said that the future of the nation lies in the existence of quality education at this time. Quality education will only emerge if there is a quality educational institution. Therefore, efforts to improve the quality of education are a strategic point in order to create quality education.